African swine fever: an unprecedented disaster and challenge to China - Tao Wang; Yuan Sun; Hua-Ji Qiu (BMC, 2018)
Abstract Background African swine fever (ASF), caused by African swine fever virus, is a hemorrhagic and often fatal disease of domestic pigs and wild boar, which is notifiable to the World Organization for Animal Health. On August 3, 2018, China reported the first outbreak of ASF in Shenyang, a northeastern city of China. As of October 8, a total of 33 ASF outbreaks were reported in eight provinces in China, the biggest pork producer and consumer in the world. Main body This commentary summarizes the current situation of ASF in China, measures that China has taken to control the disease, lessons learnt from other countries, challenges and recommendations on ASF control in China, and possible international collaborations on ASF. Conclusions ASF is an unprecedented disaster and challenge to the Chinese swine industry. It will be a formidable and protracted campaign to control ASF in China, which requires joint participation and coordination of stakeholders and agencies at different levels.